Financial Competence of Micro, Small, and Medium Enterprises in Ponorogo - Khusnatul Zulfa Wafirotin; Hadi Sumarsono (Faculty of Economics and Business, University of Pasundan, 2017)
The purpose of this study was to know and analyze the accounting capability in an effort to improve financial competence for the Micro, Small and Medium (MSM) entrepreneurs in Ponorogo. The method used was survey, through interview and observation. Accounting competence was viewed from the aspect of sales turnover, capital resources used, net income every month, financial statement preparation, financial statement preparation forms, constraints in the preparation of financial statements, and training that had been participated. The results showed the majority of MSM entrepreneurs in Ponorogo including micro-entrepreneurs and the capital resource had an income per month of < Rp 5.000.000,-. Most of them did not prepare for financial statements. The financial statement that was prepared was income statement. Most of them had also not been trained, and financial statement preparation constraints were experienced because they did not understand accounting. MSME financial competence in Ponorogo needed to be improved by accounting training, with the target of being able to prepare financial statements, bankable, increase income to develop the business. Further research was required in the formulation of modules and accounting training for target achievement.